Combustion characteristics of biogas flame from Palm Oil Mill Effluent (POME) at variable equivalence ratio - Ahmmad Shukrie, Md Yudin; A., Saat; Mohamad Firdaus, Mohd Yasin (Universiti Malaysia Pahang, 2020)
The use of different fuels in unmodified engines requires a thorough understanding of the change of combustion characteristics that are introduced by the different fuel. In the present study, the combustion characteristics of biogas at different equivalence ratio through numerical analysis are studied. A non-premixed flame is simulated based on a lab scaled burner with methane as a fuel for validation purpose. The turbulent non-premixed combustion simulation was performed by using